Isolated Avulsion Fracture of the Lesser Trochanter in Adults - CHO, HWAN SEONG (In Vivo, 2020)
Background/Aim: Isolated fractures of the lesser trochanter (LT) of adults are rare and most of them are pathologic fractures due to an underlying malignancy. The aim of our study was to provide comprehensive information on the epidemiology, etiology, diagnostic approach, and treatment algorithm of adult LT fractures. Patients and Methods: We present the cases of six patients who were treated for isolated LT fractures between November 2010 and May 2019. A literature review was performed to identify adult LT fracture cases in previous studies. Results: In two patients, the LT fracture was the first manifestation of the underlying tumors. Through a literature review, we identified 32 adults with isolated LT fractures. Among these, 27 were pathologic fractures. In 11 pathologic fractures, LT avulsion was the first manifestation of malignancy. Conclusion: Metastasis and the first manifestation of an underlying malignancy should be suspected in adult patients with isolated LT fracture. A stepwise approach can prevent misdiagnosis and offer rational treatment modality.